Patterns of Uterine Abnormalities Detected by Transvaginal Ultrasonography among Infertile Women: A Cross-Sectional Study in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Uterine abnormalities are common but often underdiagnosed contributors to female infertility, and transvaginal ultrasonography provides a sensitive, non-invasive method to detect these structural pathologies—an area particularly relevant in Bangladesh, where infertility poses a growing reproductive health challenge.Objective: This study aimed to assess the presence and pattern of uterine abnormalities using transvaginal ultrasonography (TVS) in women presenting with infertility in a tertiary care hospital of Bangladesh.Methodology: This cross-sectional study was conducted from January to December 2020 at the Department of Reproductive Endocrinology and Infertility, Dhaka Medical College Hospital. A total of 98 women presenting with infertility and undergoing routine TVS were enrolled. Women with hormonal disorders or male factor infertility were excluded. Data on sociodemographic characteristics, reproductive and menstrual history were collected through face-to-face interviews using a semi-structured questionnaire. TVS findings were also recorded.Results: The mean age of participants was 30 ± 5 (SD) years; 67.0% resided in urban areas and 69.0% had primary infertility. Menorrhagia was reported in 54% and dysmenorrhea in 26.0% of participants. TVS revealed uterine pathologies in 93.0% of cases, with acquired causes being predominant. Fibroids were the most common finding (54.0%), followed by adenomyosis (28.0%). Other acquired abnormalities included endometrial polyps (6.0%), endometrial hyperplasia (4.0%), and intrauterine adhesions (1.0%). Congenital uterine anomalies were observed in 16.0% of women, with arcuate uterus being the most frequent (11.0%). Congenital uterine pathologies were more common in participants with primary infertility (21.0% vs 8.0%), while acquired uterine causes were more frequent in participants with secondary infertility (92.0% vs. 79.0%). No statistically significant association was observed (p>0.05).Conclusion: TVS identified a high prevalence of uterine pathologies, with fibroids and adenomyosis being the most common.Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1): 81-87